Hepatoprotective effect anti-inflammatory and antioxidant Ganoderma lucidum ethanol extract on rats exposed to Plumbum acetate - Hernayanti; Laksana Agung; Saryono; Jehloh Latifah (E3S Web of Conferences)
Plumbum (Pb) is a toxic heavy metal that pollutes the environment and endangers human health. Pb exposure also induces a hepatic inflammatory response characterized by an increase in TNFα. The purpose of the study was to obtain natural anti-hepatotoxic compounds due to Pb exposure from Ganoderma extract in terms of GST, SOD, GPx, and TNF α levels. This research was conducted experimentally with a Completely Randomized Design consisting of 6 treatments with 4 replications. Twenty-four rats were used in this study and divided into six groups with four replications. Group 1 was the healthy control, and group 2 was the sick control induced by a Pb acetate dose of 0.5 mg/kgBB. Groups 3, 4, and 5 were induced by Pb acetate and given ethanol extract of G.lucidum at a dose of 250 mg/kgBW, 500 mg/kgBW, and 750 mg/kgBW for 14 days. The parameters studied include GST, TNFα, SOD, and GPx levels. Data were analyzed by the ANOVA test and continued with Duncan's test. Ganoderma lucidum is anti-hepatotoxic in terms of GST levels, anti-inflammatory in terms of TNF alpha levels, and antioxidant in terms of SOD and GPx levels. A dose of 500 mg/kgBW is a dose that can overcome the inflammatory effects of free radicals and hepatotoxic effects due to Pb exposure.